A BIBLIOMETRIC REVIEW OF BOARD DIVERSITY AND FIRM PERFORMANCE. MAPPING THE INTELLECTUAL STRUCTURE AND EMERGING TRENDS - Rajespari, K.; Mohamad, Zam Zuriyati; Zakaria, Zuriawati (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The connection between board diversity as well as firm performance has received growing scholarly attention in recent years, driven by increasing awareness of corporate governance reforms, gender inclusivity, and sustainable business practices. Despite the volume of research, the intellectual structure and knowledge development within this area remain fragmented, calling for a systematic bibliometric investigation. This research discusses this gap by evaluating the global research trends on board diversity as well as firm performance through a comprehensive bibliometric approach. Data were collected using Scopus advanced searching with carefully selected keywords, yielding a final dataset of 318 documents. The dataset was further processed using OpenRefine to clean and harmonize author names, keywords, as well as institutional information, guaranteeing consistency and accuracy. Bibliometric indicators, citation patterns, and productivity measures were generated using the Scopus Analyzer to provide statistical insights and graphical representations. Additionally, VOSviewer software was applied to map co-citation, co-authorship, as well as keyword co-occurrence networks, enabling the visualization of research clusters, collaborations, and emerging themes. The findings highlight a constant increase in publications over the last decade, with notable contributions from developed economies such as the United Kingdom, the United States, and China, alongside growing interest from emerging markets. Highly cited articles predominantly focus on gender diversity, governance mechanisms, and their direct and indirect effects on firm performance. Keyword analysis revealed critical research hotspots, including “corporate governance,” “board gender diversity,” “financial performance,” “CSR,” and “sustainable development,” which form the foundation of this scholarly discourse. This study contributes to the body of knowledge by identifying influential authors, countries, and thematic clusters while providing a roadmap for future research on how diverse boards shape firm outcomes in different institutional and cultural contexts.